Biografie pisarzy w szkolnym nauczaniu literatury w latach 1800-1863 = The biographies of writers in the teaching of literature at schools in the years 1800-1863 - Łojek, Mieczysław (1930-2015) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article illustrates the reoords of the fight for the privilege of teaching Polish literature under severe oppression. Polish teachers considered their national literature as a shield which successfully protected and stimulated the spirit of the nation. As we know, literature provides "us" with a great variety of customs and traditions, expresses patriotic feeling, displays people's aspirations, presents heroes of great moral independence, cultivates, improves and widely spreads the motber tongue.
Keywords: literatura; nauczanie; biografie; pisarze polscy; 19 w.